Karakter Agronomi Dan Satuan Panas Padi Varietas Unggul Pada Berbagai Dosis Nitrogen Di Lahan Pasang Surut - Nur I. Ariyani; Dewi E. Adriani; Gusti Rusmayadi (Universitas Lambung Mangkurat, 2020)
Rice is the staple food of Indonesian people and part of the world community. Indonesia, with a population growth rate of around 1.3-1.5% per year, requires additional rice production of about 1,8- 3 million tons of rice per year. This additional production can be achieved by using tidal swampland which is quite a large area in South Kalimantan. However, one of the obstacles in tidal swampland is the lack of nitrogen (N). N is a macronutrient that becomes the main limiting factor for plant growth as it is needed most among other nutrients. This study aimed to determine the agronomic traits of superior varieties at various N concentration. The experiment used a Split plot design with N concentration as the main plot and three rice varieties as sub-plots, while the environmental design used Randomized Block Design based on the direction of water flow. The agronomic characters observed were the number of leaves, number of tillers, plant height, the total number of panicles per plant, 1000 filled grains dry weight rice, and yield (t ha-1). The results showed that different varieties affected the plant height, number of leaves, number of tillers, the weight of 1000 grains of filled grain with IPB3S and IPB Batola 6R as the best variety, and the concentration treatment effect total of rice tillers, total of rice leaves and total number of per plant with 300 t N ha-1 as the best concentration.